2015
DOI: 10.1016/j.jbankfin.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Reward-risk momentum strategies using classical tempered stable distribution

Abstract: We implement momentum strategies using reward-risk measures as ranking criteria based on classical tempered stable distribution. Performances and risk characteristics for the alternative portfolios are obtained in various asset classes and markets. The reward-risk momentum strategies with lower volatility levels outperform the traditional momentum strategy regardless of asset class and market. Additionally, the alternative portfolios are not only less riskier in risk measures such as VaR, CVaR and maximum draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…Similarly, Novy‐Marx (2012) reported significant intermediate‐term (in a term between 7 and 12 months) momentum returns that were consistent in equity indices, currency and commodity markets. Choi, Kim, and Mitov (2015) employed various reward–risk measures (i.e. VaR, CVaR and Carhart's four factor model) and reported that momentum with lower volatility outperformed other traditional momentum strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Novy‐Marx (2012) reported significant intermediate‐term (in a term between 7 and 12 months) momentum returns that were consistent in equity indices, currency and commodity markets. Choi, Kim, and Mitov (2015) employed various reward–risk measures (i.e. VaR, CVaR and Carhart's four factor model) and reported that momentum with lower volatility outperformed other traditional momentum strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, seasonal return patterns became clear. Previous studies, conducted for the German market by Nagler (1979) and Hanel (1991), referred equally to the superiority of the momentum strategy (see also Schiereck and Weber, 1995;Hirshleifer and Shumway, 2003; Barroso and Santa-Clara, 2015; Choi et al, 2015;Bohl et al, 2016).…”
Section: Scientific Discussion Of the Momentum Strategymentioning
confidence: 99%
“…To find out whether the FSCORE also affects the portfolios' crash risk exposures, we calculate the maximum drawdown (MDD) statistics for all 75 of the portfolios examined based on their month-end values. Similar to Choi et al (2015), MDD is defined as the maximum percentage loss over any subinterval of the evaluation period. Table 5 shows that MDD statistics are consistent with the return generation patterns reported for bearish periods (bearish months) with respect to the strongest impact of the FSCORE boost on average MDDs clearly being documented for the annually re-formed portfolios, among which the average MDD decreases from − 52.42 to − 45.31% as a consequence of including the high-FSCORE criterion alongside the primary criteria.…”
Section: Crash Risk Exposurementioning
confidence: 99%